The role of geographic information systems (GIS) in decision-making for the localization of industrial areas and the evaluation of existing industrial areas (an applied study in the Nador province) - El Monhim Bilal; Sbai Abdelkader; Arabi Mourad; Makkaoui Mohamed; Hlal Mohammed; Benrbia Khadija (E3S Web of Conferences)
The study presents a comprehensive analysis of industrial localization in Nador Province, northeastern Morocco. By employing a descriptive and analytical methodology, we have thoroughly examined the province's natural and human data, diagnosing all indicators influencing the process of industrial localization. Our comprehensive approach has classified the area based on its suitability for industrial localization, ranging from ideal to unsuitable regions. The ideal areas for manufacturing, estimated to cover approximately 1,469 hectares, represent 0.5% of the province's total area. The suitable areas for establishing industrial units, estimated to cover 14,211 hectares, represent 5.4% of the province's total area. These comprehensive findings, which encompass several municipalities, such as Selouane, Al Aroui, Ouled Settout, Beni Ansar, and Zaio, provide a robust foundation for policymakers, urban planners, and industrial stakeholders. Furthermore, our correlation between the current industrial zones delineated in the direction plan, Nador Horizon 2040, and the outcomes derived from the spatial analysis of industrial localization factors using geographic information systems (GIS), adds to the validity and comprehensiveness of our research.